Trade and trade policies in Eastern and Southern Africa - Subramanian, Arvind; Elborgh-Woytek, Katrin; Gelbard, Enrique; Harmsen, Richard; Nagy, Piroska Mohácsi 1957- (International Monetary Fund, 2000)
Since the early 1990s, many countries in sub-Saharan Africa have made significant progress in opening their economies to external competition through trade and currency liberalization. This paper analyzes trade and policy developments for 22 countries in eastern and southern Africa, looks at regional and multilateral integration issues, and reflects on the main challenges these countries face in the new decade. It addresses the main trade policy issues for these countries and suggests possible actions they and their trading partners could follow
Keywords: Liberalisierung; Außenhandelspolitik; Africa, Eastern; Commerce; Foreign economic relations; Africa, Southern